2008
DOI: 10.1111/j.1750-3841.2008.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Color, Pigment, and Phenolic Stability in Yogurt Systems Colored with Nonacylated Anthocyanins from Berberis boliviana L. as Compared to Other Natural/Synthetic Colorants

Abstract: Anthocyanins are of interest to the food industry because of their antioxidant power, attractive color, and stability in high acid foods. Powder from the Peruvian berry Berberis boliviana Lechler, rich in nonacylated anthocyanins (7% to 8% dry weight), was incorporated into yogurt samples containing 3 different fat levels. Color (CIE L, a, b, chroma, and hue angle), pigment (monomeric anthocyanin and polymeric color), and total phenolics were monitored over 8 wk of storage and compared to yogurt treatments con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
74
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 20 publications
15
74
1
1
Order By: Relevance
“…This was substantiated by the increase in color saturation as shown in the C value and % Color Retention obtained within the two weeks of storage. Similar results were obtained in the study on the retention of Berberis boliviana anthocyanin applied in yogurt (Wallace and Giusti, 2008) and yogurt supplemented with natural betacyanin extract from Opuntia soehrensii seeds stored at 4 o C for four weeks (Caldas-Cueva et al, 2016). This could be again due to the lowering of the pH of yogurt.…”
Section: Color Characteristics and Retention Of Pili Pigment Extractsupporting
confidence: 76%
See 2 more Smart Citations
“…This was substantiated by the increase in color saturation as shown in the C value and % Color Retention obtained within the two weeks of storage. Similar results were obtained in the study on the retention of Berberis boliviana anthocyanin applied in yogurt (Wallace and Giusti, 2008) and yogurt supplemented with natural betacyanin extract from Opuntia soehrensii seeds stored at 4 o C for four weeks (Caldas-Cueva et al, 2016). This could be again due to the lowering of the pH of yogurt.…”
Section: Color Characteristics and Retention Of Pili Pigment Extractsupporting
confidence: 76%
“…Interestingly, in the study of Arslan and Bayrakci (2016), phenolic contents and antioxidant activity of persimmon-supplemented yogurt were enhanced after two weeks of storage. Phenolic stability was also observed in yogurt containing Berberis boliviana anthocyanin over an eight-week refrigerated storage (Wallace and Giusti, 2008). These prove that the functional colorant from fruit and vegetable pigments would certainly add value to healthy products such as yogurt.…”
Section: Color Characteristics and Retention Of Pili Pigment Extractmentioning
confidence: 61%
See 1 more Smart Citation
“…Based on our preliminary characterisation of the pigments, a study was performed to determine the feasibility of using the pigments as food colourants (Wallace & Giusti, 2008). Our results indicated that this berry could work as a natural colourant for yogurt, making it more relevant to report a complete identification of the pigments.…”
Section: Introductionmentioning
confidence: 95%
“…Fruits of Berberis sp. are edible and rich in vitamin C and contain a large amount anthocyanin (Wallace and Giusti 2008;Akbulut et al 2009;Parichehr and Golkho 2009). Anthocyanins and other phenolic compounds are potent scavengers of free radicals, although they can also behave as pro-oxidants (Konczak and Zhang 2004).…”
Section: Introductionmentioning
confidence: 99%